Caring for the caregivers - a nursing management perspective - A Minnaar (AOSIS, 2001)
The aim of the study was to explore the practice of caring for the caregivers in selected hospitals in KwaZulu-Natal. A qualitative research approach was used to ensure that the complexities of caring were reflected in the study. The qualitative analysis of the interviews with nurse managers and nurses indicated that they saw caring as an important part of their management task. The participants in the study saw caring for nurses mainly as dealing with the interpersonal aspects of nurses. Caring for nurses was further described in terms of solving the personal problems of nurses, promoting the development and growth needs of nurses with the focus, mainly, on the educational needs of the organisation itself, the welfare needs of nurses with specific reference to their family needs and responsibilities, and a major emphasis on HIV/AIDS issues arising amongst nurses themselves. Die